Discourse Analysis on Philosophy from the point of view of Interactional Sociolinguistics Approach - J Sutomo (Universitas Stikubank (UNISBANK) Semarang, 2013)
This study focuses on the discourse analysis on casualconversation in “philosophy,” from the point of view of interactional sociolinguisticsapproach. The purpose is to analyze theinteractional patterns in casual conversation through which interactants jointly construct social relations. I limit the study just on the analysisof the grammatical patterns at the clause level which indicate power andsubordination within interaction. The approach of this study is qualitative method and theunderlying theoryisEggins’s AnalyzingCasual Conversation, thegrammar of casual conversation: enacting role relations. The result of the analysis shows that two participants (Bradand Fran) are dominant while one participant (Dave) is theincidental participant. The percentage of turns produced in the casualconversation is: Brad = 50% , Fran = 33%, and Dave 17%.Keywords: discourse analysis, casualconversation, interactional sociolinguistics.